2013
DOI: 10.1021/ja310255s
|View full text |Cite
|
Sign up to set email alerts
|

Directly Probing the Effects of Ions on Hydration Forces at Interfaces

Abstract: Understanding the influence of water layers adjacent to interfaces is fundamental in order to fully comprehend the interactions of both biological and nonbiological materials in aqueous environments. In this study, we have investigated hydration forces at the mica-electrolyte interface as a function of ion valency and concentration using subnanometer oscillation amplitude frequency modulation atomic force microscopy (FM-AFM). Our results reveal new insights into the nature of hydration forces at interfaces due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
145
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 45 publications
11
145
3
Order By: Relevance
“…Our rationale for estimating an effective separation (h eff ) is that the AFM cantilever cannot exert a sufficient pressure to desolvate the ions (i.e., penetrate nearby hydration layers), and thus leaves the adsorbed hydrated ions between the tip and substrate intact (see SI Appendix for details). This estimate is consistent with the dependence of pressure on mica-mica separation determined in previous SFA experiments (16). The hydrated ions lead to h eff of ∼2× the hydrated ion diameter (see SI Appendix, Fig.…”
Section: Significancesupporting
confidence: 91%
See 1 more Smart Citation
“…Our rationale for estimating an effective separation (h eff ) is that the AFM cantilever cannot exert a sufficient pressure to desolvate the ions (i.e., penetrate nearby hydration layers), and thus leaves the adsorbed hydrated ions between the tip and substrate intact (see SI Appendix for details). This estimate is consistent with the dependence of pressure on mica-mica separation determined in previous SFA experiments (16). The hydrated ions lead to h eff of ∼2× the hydrated ion diameter (see SI Appendix, Fig.…”
Section: Significancesupporting
confidence: 91%
“…Near-surface solvent structure and interaction forces between surfaces (such as those of mica plates) have been investigated via atomic force microscopy (AFM) (16), surface force apparatus (SFA) (13,17,18), and theoretical modeling (19,20). Those studies showed there are at least three minima in force vs. distance between two mica surfaces that exhibit a periodicity of about 3 Å corresponding to the approximate thickness of a water…”
mentioning
confidence: 99%
“…These may include poorly reproducible curves and amplitude vs distance curves that significantly deviate from a typical sigmoidal shape 42 . If contaminants, ionic or otherwise, are dispersed homogeneously throughout the fluid, they may not show up in topographic imaging but could disrupt the hydration structure of the sample 69 , which is crucial for maintaining a regular tip-sample interaction 29 and obtaining high resolution 70 . There may also be direct effects of the contaminants on the sample, especially in soft, biological experiments.…”
Section: Discussionmentioning
confidence: 99%
“…118 Other exciting opportunities to apply in situ AFM techniques towards photoelectrochemistry include in situ patterning and modification of electrode surfaces 117,119 and elucidation of the electrolyte double layer structure and its associated charge at electrode surfaces. [120][121][122][123][124][125] Of particular interest are recent AFM studies that have demonstrating the ability to obtain three-dimensional (3D) force maps at a solid-liquid interface that reveal hydration layer structure and dynamics with Angstrom-and sub-minute resolutions, respectively. 122,125 When applied to studying a photoelectrode surface, this application of AFM could be invaluable, not only for better understanding electrochemical charge transfer kinetics, but also the affect that charged species in the electrolyte may have on the space charge layer of photoelectrodes.…”
Section: Atomic Force Microscopymentioning
confidence: 99%